USING FLIPPED CLASSROOM MODELS IN TEACHING SPEAKING AT SMA 12 GOWA : FLIPPED CLASSROOM, SPEAKING,CLASSROOM - Zikrillah, Andi; Ariana; Basir, Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research describe the use of the flipped classroom method in English learning. The aims of this study was to see how to improve students' speaking skills through the flipped classroom model using recount text as a treatment tool. This study was conducted at SMAN 12 Gowa with the subject of the research being the students of class X MIPA 1 which consist of 27 students. This research design used a pre-experimental one group pre-test post-test design. The results of this research indicate that, there is a comparison of the pre-test and post-test results which show that students' speaking ability before using the flipped classroom method is still lacking, while at the post-test stage students' speaking ability has increased significantly.. It can be proven from the results of the mean values ​​of grammar, fluency, and vocabulary, the mean speaking value can be obtained. The mean speaking value before the test was around 31.20, while the mean value after the test was 78.40, with the test results after the test increasing. Based on these data, it can be concluded that there is an increase in student learning outcomes by implementing flipped classes on speaking skills